Clinical Characteristics and Outcomes of Late Relapse in Stage I Testicular Seminoma. Issue 10 (October 2016) - Hosni, A.; Warde, P.; Jewett, M.; Bedard, P.; Hamilton, R.; Moore, M.; Nayan, M.; Huang, R.; Atenafu, E.G.; O'Malley, M.; Sweet, J.; Chung, P.
Abstract: Aims: To identify the characteristics and outcomes associated with late relapse in stage I seminoma. Materials and methods: A retrospective review was carried out of all patients with stage I seminoma managed at our institution between 1981 and 2011. Data were obtained from a prospectively maintained database. Late relapse was defined as tumour recurrence > 2 years after orchiectomy. Results: Overall, 1060 stage I seminoma patients were managed with active surveillance ( n = 766) or adjuvant radiotherapy ( n = 294). At a median follow-up of 10.6 years (range 1.2–30), 142 patients relapsed at a median (range) of 14 (3–129) months; 128 on active surveillance and 14 after adjuvant radiotherapy. The late relapse rate for the active surveillance and adjuvant radiotherapy groups was 4% and 1%, respectively. There was no specific clinicopathological factor associated with late relapse. Isolated para-aortic node(s) was the most common relapse site in active surveillance patients either in late (88%) or early relapse (82%). Among the active surveillance group, no patients with late relapse subsequently developed a second relapse after either salvage radiotherapy ( n = 25) or chemotherapy ( n = 6), whereas in early relapse patients a second relapse was reported in seven (10%) of 72 patients treated with salvage radiotherapy and one (4%) of 23 patients who received chemotherapy; all second relapses were subsequently salvaged with chemotherapy. No patient in the adjuvant radiotherapy group developed a second relapse after salvage chemotherapy ( n = 10) or inguinal radiotherapy/surgery ( n = 4). Of seven deaths, only one was related to seminoma. Among active surveillance patients, the 10 year overall survival for late and early relapse groups were 100% and 96% ( P = 0.2), whereas the 10 year cancer-specific survival rates were 100% and 99% ( P = 0.3), respectively. Conclusions: In stage I seminoma, the extent and pattern of late relapse is similar to that for early relapse. For active surveillance patients, selective use of salvage radiotherapy/chemotherapy for relapse results in excellent outcomes regardless of the timing of relapse, whereas salvage radiotherapy for late relapse seems to be associated with a minimal risk of second relapse. Highlights: Clinical characteristics and outcomes of late and early relapse were similar. 10-year overall survival of late relapsed patients on active surveillance was 100%. Radiotherapy is effective salvage for late relapse on active surveillance.